Problem issues of organizing general education for prisoners - Kondratov, D. Y.; Shevelev, K. Y.; Tur, I. Y. (Аналітично-порівняльне правознавство, 2025)
The article attempts to outline the problematic issues of organizing general education for persons sentenced to imprisonment. It has been stated that the right to education is a constitutional right of any citizen, in particular, Article 53 of the Constitution of Ukraine enshrines this subjective right in our state for everyone, and those sentenced to imprisonment are not an exception. Thus, the right of convicts to education occupies an important place in the system of their rights, since it ensures the comprehensive development of the individual as the highest social value of society. However, the mechanism for implementing the aforementioned right in relation to convicts has its own peculiarities. The leading role of education lies in the fact that when prisoners are involved in the educational process, it primarily distracts them from useless, meaningless pastimes, and also helps them rethink their life positions. Based on this, the authors argue that increasing the cultural level of convicts in the process of education contributes to some extent to a positive change in their personality. It has been established that although the right to education of persons sentenced to imprisonment is limited in some way, these restrictions do not apply to obtaining a complete general secondary education. The authors analyzed the current legislation regulating the procedure for organizing general education for prisoners in Ukraine. Based on this analysis, it was found that the provisions of the basic Law of Ukraine «On Education» establish the organizational foundations and principles of state policy in the field of education, state guarantees of human and citizen rights in this area, and the priority of education in the field of social development. The Law of Ukraine «On General Secondary Education» regulates the entire system of general secondary education, almost the entire range of issues related to the functioning of the general secondary education sector. A special regulatory document regulating the procedure for organizing general education for prisoners in Ukraine is the «Procedure for Organizing Complete General Secondary Education by Prisoners Sentenced to Imprisonment for a Certain Term or Life Imprisonment, as Well as Minors Taken into Custody». The authors of the article note that at present the state of the organization of general education in penal institutions, although it has certain positive trends, cannot be recognized as fully complying with international recommendations on this issue, therefore the modernization of education remains an important component of modern penal policy in Ukraine.